Method for producing iron-based crystal alloy

The (Fe, Co) 100-x (B, C) x composition and rapid cooling process address the limitations of existing alloys by achieving high saturated magnetic flux density and low iron loss, enabling efficient BLDC motors.

JP2025016054AActive Publication Date: 2025-01-31NEXT CORE TECHNOLOGIES INC
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
JP2023119069
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-07-21
Publication Date
2025-01-31
Estimated Expiration
2043-07-21

AI Technical Summary

Technical Problem

Existing iron-based alloys, such as FE-Si-B amorphous and nano crystal materials, face challenges in achieving high saturated magnetic flux density (Bs ≧ 1.7T) and low iron loss, making them unsuitable for high-efficiency BLDC motors, particularly for EV applications, due to processing difficulties and limitations in magnetic characteristics.

Method used

A composition formula of (Fe, Co) 100-x (B, C) x with specific ratios (10.0 ≦ x ≦ 18.0 atom, 0.05 ≦ y ≦ 0.5, 0.0 ≦ z ≦ 0.3) is used, combined with a rapid cooling process involving a single roll-melting and cooling system to produce an iron-based crystal alloy with a 50% α-FE phase and FE-B phase, ensuring high Bs and low iron loss.

Benefits of technology

The solution enables the production of iron-based crystal alloys with Bs ≧ 1.7T, iron loss ≤ 20W/kg, and permeability ≥ 1500 at 1 kHz, suitable for high-efficiency BLDC motors, overcoming processing difficulties and enhancing motor performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025016054000001_ABST
    Figure 2025016054000001_ABST
Patent Text Reader

Abstract

To provide a method for producing ion-based crystal alloy, the method enabling the ion-based crystal alloy to be easily punched and enabling the alloy to secure low iron loss and high saturation magnetic flux density.SOLUTION: A method for producing ion-based crystal alloy includes: a step of preparing (Fe, Co)-B-based alloy molten metal 3 having a composition which is represented by composition formula (Fe1-yCoy)100-x(B1-zCz)x, where x, y and z satisfy 10.0≤x≤18.0 atom%, 0.05≤y≤0.5, and 0.0≤z≤0.3; and a quenching and solidifying step of quenching and solidifying the alloy molten metal 3 on a cooling roll 8, wherein the quenching and solidifying step includes a step of injecting the alloy molten metal 3 onto the surface of the cooling roll 8 from a tapping nozzle 6 while rotating the cooling roll 8 at a roll surface speed of 15 m / sec or more and 40 m / sec or less, and thereby manufacturing an ion-based crystal alloy 9 having an abundance ratio of an α-Fe phase of 50 vol.% or more and less than 95 vol.%, and containing the balance Fe-B phase.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to an iron-based crystalline alloy and a method for producing the same, and more particularly to an iron-based crystalline alloy that can be suitably used as a core material for a DC motor, and a method for producing the same. [Background technology]

[0002] In recent years, the market has been demanding materials with low iron loss and high saturation magnetic flux density for various passive elements and transformers, such as inductors and reactors used as electronic components. Such materials include iron-based amorphous materials and iron-based nanocrystalline materials, which are made primarily from iron (Fe), silicon (Si), and boron (B). Demand for Fe-Si-B amorphous alloy ribbons with a thickness of about 17 to 25 μm, which are produced using such soft magnetic materials by the molten metal rapid solidification method, is increasing mainly for large transformers and inductors as an alternative to conventional silicon steel sheets.

[0003] In addition, because the Fe-Si-B amorphous alloy ribbon has lower core loss than silicon steel sheet, it is being considered to utilize this feature to improve motor efficiency by applying it to the rotor core and stator core of a brushless direct current (BLDC) motor. In particular, when used in a high-speed BLDC motor that exceeds 20,000 rpm, high motor efficiency can be obtained because the operating range of the soft magnetic material is in the high-frequency band of around 2 kHz, so it is expected to be used in white goods such as vacuum cleaners and auxiliary motors for electrical equipment, which require high-speed motor rotation.

[0004] Meanwhile, drive motors for EVs, which require even higher efficiency than motors for white goods, cannot obtain the necessary output unless they can secure a saturation magnetic flux density (Bs) equivalent to that of silicon steel sheet, but the maximum Bs of Fe-Si-B amorphous alloys is around 1.6 T, making it difficult to replace silicon steel sheets, which have a Bs of 1.7 T or more. For this reason, there have been no examples to date of EV drive BLDC motors using Fe-Si-B amorphous alloys being brought to the market.

[0005] In the past, BLDC motors for driving EVs in the tens of kW class or higher have been made more efficient by combining silicon steel core material with anisotropic rare earth iron boron sintered magnets, which exhibit excellent permanent magnetic properties, and utilizing magnet torque, but silicon steel, which has low magnetic permeability, cannot fully utilize the excellent magnetic properties of anisotropic rare earth iron boron sintered magnets, making it difficult to realize a low iron loss core material.For this reason, there is extremely high market demand for high-output, high-efficiency BLDC motors that can contribute to energy savings in automobiles through the synergistic effect of effectively utilizing permanent magnet performance and reducing iron loss in the core material.

[0006] Fe-Si-B amorphous alloys have a higher magnetic permeability than silicon steel sheets and can reduce iron loss to about 1 / 10, so they are being considered as a replacement for silicon steel sheets as a core material for BLDC motors for driving EVs. However, because of the low saturation magnetic flux density (Bs) as mentioned above, they are mainly used in high-speed BLDC motors with a rotation speed of 15,000 rpm or more, where the effect of iron loss becomes significant, and it is difficult to apply them to EV drive motors with a rotation speed of less than 15,000 rpm. In addition, Fe-Si-B amorphous alloy ribbons are thin, about 25 μm thick, and it is difficult to perform punching press processing to manufacture laminated cores for rotor cores and stator cores of BLDC motors, so they are mainly limited to use as wound cores, making it difficult to replace silicon steel sheets in motor applications.

[0007] On the other hand, Fe-Si-B nanocrystalline materials are prone to cracking and chipping, so they can only be used as wound cores or crushed and then molded into pressed powder cores; like Fe-Si-B amorphous alloys, it is difficult to use them as laminated cores.

[0008] To obtain an Fe-Si-B system amorphous structure or nanocrystalline structure, it is necessary to add Si and B, and to obtain a nanocrystalline structure, additional elements such as Cu and Nb are required, which results in a decrease in the composition ratio of Fe, making it impossible to obtain Bs ≧ 1.7 T. For this reason, no iron-based alloy has been found to date that can be easily made into a laminated core and that can ensure Bs ≧ 1.7 T.

[0009] For example, Non-Patent Document 1 discloses that the addition of phosphorus (P) reduces the quenching solidification rate and produces an iron-based amorphous alloy ribbon with a thickness of 50 μm or more. However, phosphorus-added alloys not only cause a decrease in Bs due to the addition of phosphorus, but also have the risk of causing significant contamination inside and outside the molten metal quenching device due to the volatilization of the phosphorus component during alloy melting, and are also flammable, so there are still few examples of their application in the industrial field.

[0010] Patent Documents 1-3 disclose a method for producing an amorphous alloy ribbon having a thickness (e.g., about 50 μm) that allows punching by a multiple slit method in which molten alloy is poured from multiple slit nozzles onto a rotating cooling roll. However, even with such a technique, it is difficult to achieve Bs≧1.7T, and it is difficult to apply it as a soft magnetic material for laminated cores for BLDC motors that drive EVs to replace silicon steel sheets.

[0011] Patent Document 4 discloses a method for manufacturing a metal ribbon using a multi-hole nozzle to prevent the thickness of the metal ribbon from becoming non-uniform when a wide quenched ribbon is produced. The invention of Patent Document 4 is characterized by the shape of the nozzle opening, but there is a problem that the nozzle processing cost rises due to the difficulty of processing, making it difficult to use on a mass production level.

[0012] Patent Document 5 discloses a method for producing an iron-based silicon boron-based amorphous alloy using a discharge nozzle with a staggered multi-orifice to produce a thick plate. However, compared to silicon steel plate, it is difficult to ensure a high Bs and sufficient thickness.

[0013] Patent Document 6 discloses an Fe-Si-B based rapidly solidified alloy that can be made into a laminated core and is characterized by a high Bs of Bs≧1.7T and a thickness of ≧40 μm. The invention of Patent Document 6 optimizes the compounding ratio of each element in the ternary composition of the essential elements iron, silicon, and boron, but the workability of the punching press used to manufacture a laminated core from the alloy ribbon obtained in this way is inferior to that of silicon steel plate, so there is room for further improvement in terms of manufacturing laminated cores at low cost. [Prior art documents] [Patent documents]

[0014] [Patent Document 1] Japanese Patent Application Publication No. 5-329587 [Patent Document 2] Japanese Patent Application Publication No. 7-113151 [Patent Document 3] Japanese Patent Application Publication No. 8-124731 [Patent Document 4] Japanese Patent Application Publication No. 63-220950 [Patent Document 5] JP 2018-153828 A [Patent Document 6] JP 2021-193199 A [Non-patent literature]

[0015] [Non-Patent Document 1] Creation of new bulk metallic glass / amorphous thick plates with high saturation magnetic flux density (Tohoku University, Metallic Glass Research Center) Akihiro Makino, Ken Kubota, Tono Chuntao Summary of the Invention [Problem to be solved by the invention]

[0016] An object of the present invention is to provide an iron-based crystalline alloy that can be easily punched while ensuring low core loss and high saturation magnetic flux density, and a method for producing the same. [Means for solving the problem]

[0017] The object of the present invention is to provide a compound having the formula (Fe 1-y Co y ) 100-x (B 1-z C z ) x where x, y, and z satisfy 10.0≦x≦18.0 atomic %, 0.05≦y≦0.5, and 0.0≦z≦0.3, respectively, the abundance ratio of α-Fe phase is 50 volume % or more and less than 95 volume %, and the balance is an iron-based crystalline alloy consisting of Fe-B phase.

[0018] This iron-based crystalline alloy preferably has a saturation magnetic flux density of 1.7 T or more, an iron loss (W10 / 1k) of 20 W / kg or less at a magnetic flux of 1.0 T and a frequency of 1 kHz, and a magnetic permeability of 1500 or more at 1 kHz.

[0019] The object of the present invention is to provide a composition of formula (Fe 1-y Co y ) 100-x (B 1-z C z ) x and a rapid solidification step of rapidly solidifying the molten alloy on a chill roll, the rapid solidification step being performed by rotating the chill roll at a roll surface speed of 15 m / sec or more and 40 m / sec or less, while ejecting the molten alloy from a discharge nozzle onto the surface of the chill roll, thereby producing an iron-based crystalline alloy in which the abundance ratio of α-Fe phase is 50 volume % or more and less than 95 volume %, and the remainder being Fe-B phase. Effect of the Invention

[0020] According to the present invention, it is possible to provide an iron-based crystalline alloy that can be easily punched while ensuring low core loss and high saturation magnetic flux density, and a method for producing the same. [Brief description of the drawings]

[0021] [Figure 1] 1 is a schematic diagram of an apparatus used in a method for producing a ribbon-shaped iron-based crystalline alloy according to an embodiment of the present invention. [Diagram 2] 2 is an enlarged view showing a main part of the device shown in FIG. 1, where (a) is a cross-sectional view and (b) is a bottom view. [Diagram 3] 1 is a powder X-ray diffraction profile of an iron-based crystalline alloy obtained in one embodiment of the present invention. [Figure 4] 1 is a powder X-ray diffraction profile of an iron-based crystalline alloy obtained in another embodiment of the present invention. [Diagram 5] 1 is a powder X-ray diffraction profile of an iron-based crystalline alloy obtained in still another example of the present invention. [Figure 6] 1 is a powder X-ray diffraction profile of an iron-based crystalline alloy obtained in a comparative example of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0022] [Alloy composition] To improve the punchability of iron-based alloys, it is necessary to make them crystalline rather than amorphous, which is hard and easily broken. The composition of the iron-based crystalline alloy of the present invention is based on a binary Fe-B alloy composition, with part of the Fe replaced by Co, which is a ferromagnetic element like Fe, and has the composition formula (Fe 1-y Co y ) 100-x (B 1-z C z ) x It is expressed as:

[0023] If the substitution rate of Co for Fe is too low, it becomes difficult to achieve Bs≧1.7T, so the y in the above composition formula must be 0.05 or more. As the value of y increases, the Bs of the iron-based crystal alloy increases monotonically up to y=0.5, but when the value of y exceeds 0.5, Bs does not increase and only the manufacturing cost increases due to the use of Co, which is an expensive element. For this reason, 0.05≦y≦0.5 is satisfied, and from the viewpoint of achieving a high Bs, 0.1≦y≦0.5 is preferable, and from the viewpoint of manufacturing costs, 0.15≦y≦0.4 is more preferable.

[0024] In the iron-based crystalline alloy of the present invention, B is an essential element for obtaining low core loss and high magnetic permeability, and plays a role in forming a uniform fine structure consisting of the α-Fe phase and the Fe-B phase. A part of B may be replaced with C, which lowers the melting point of the molten alloy, easing the rapid solidification conditions and facilitating the production of the iron-based crystalline alloy.

[0025] However, if the substitution rate of C for B is too high, Fe-C compounds are generated, making it difficult to obtain a uniform and fine crystal structure consisting of α-Fe phase and Fe-B phase. For this reason, z in the above composition formula is 0.0≦z≦0.3, and from the viewpoint of maintaining high Bs characteristics, 0.0≦z≦0.2 is preferable, and 0.05≦z≦0.15 is more preferable.

[0026] If the ratios of B and C to the overall composition of the iron-based crystalline alloy are too low, coarse α-Fe phases that become the starting points of cracks during punching press are likely to precipitate, whereas if the ratios of B and C to the overall composition of the iron-based crystalline alloy are too high, the volume ratio of the Fe-B phase increases and the volume ratio of the α-Fe phase decreases, making it difficult to ensure Bs ≧ 1.7 T. For this reason, x in the above composition formula is 10.0≦x≦18.0 atomic %, preferably 11.0≦x≦17.0 atomic %, and more preferably 12.0≦x≦16.0 atomic %.

[0027] [Metal structure] The iron-based crystal alloy of the present invention is a (Fe,Co)-B-based iron-based crystal alloy having a composite structure of an α-Fe phase and an Fe-B phase, and has magnetic and mechanical properties that greatly contribute to improving the efficiency of a BLDC motor. If the abundance ratio of the α-Fe phase is too low, it becomes difficult to ensure Bs≧1.7T, while if it is too high, coarse α-Fe of about 10 μm or more is likely to precipitate, which may become the starting point of cracks during punching press, and furthermore, it is likely to cause an increase in iron loss and a decrease in magnetic permeability. Therefore, the abundance ratio of the α-Fe phase is 50% by volume or more and less than 95% by volume, preferably 60% by volume or more and less than 90% by volume, and more preferably 60% by volume or more and less than 85% by volume. The Fe-B phase is the remaining phase of the α-Fe phase, and is a phase mainly composed of FeB and Fe2B. As will be described later, the abundance ratio and crystal grain size of the α-Fe phase can be adjusted to a desired value by controlling the quenching speed of the molten alloy.

[0028] [Magnetic properties] The iron-based crystalline alloy of the present invention has a saturation magnetic flux density of Bs≧1.7T, but when considering application to a BLDC motor for driving an EV of 30 kW or more, Bs≧1.72T is preferable, and Bs≧1.75T is even more preferable.

[0029] In addition, the iron-based crystalline alloy of the present invention has an iron loss (W10 / 1k)≦20W / kg at a magnetic flux of 1.0T and a frequency of 1kHz, which is significantly lower than the iron loss (W10 / 1k): 96.6W / kg of silicon steel plate (JIS standard 35A360). If the iron loss (W10 / 1k) exceeds 20W / kg, the improvement effect of the motor efficiency decreases. To further improve the improvement effect of the motor efficiency, the iron loss (W10 / 1k)≦15W / kg is preferable, and the iron loss (W10 / 1k)≦10W / kg is even more preferable.

[0030] The iron-based crystalline alloy of the present invention has a magnetic permeability of 1500 or more at 1 kHz. If the magnetic permeability at 1 kHz is lower than 1500, the advantage over silicon steel plate is reduced in terms of the amount of magnetic flux on the surface of the teeth in the stator core. In order to further increase the advantage over silicon steel plate, the magnetic permeability at 1 kHz is preferably 2000 or more, and more preferably 3000 or more.

[0031] [Method of manufacturing iron-based crystalline alloy] The iron-based crystalline alloy of the present invention is produced by a method for producing an iron-based crystalline alloy, the method including the steps of preparing a molten (Fe,Co)-B-based alloy having the above-mentioned composition, and rapidly solidifying the prepared molten alloy.

[0032] Fig. 1 is a schematic diagram of a single-roll molten metal quenching apparatus used in a manufacturing method of an iron-based crystalline alloy according to one embodiment of the present invention. The single-roll molten metal quenching apparatus 1 shown in Fig. 1 includes a melting furnace 2, a molten metal storage vessel 5, and a cooling roll 8.

[0033] The melting furnace 2 supplies the molten alloy 3, which is obtained by melting the raw materials by high-frequency induction heating, to a molten alloy storage container 5 by rotating a tilting shaft 4. The molten alloy storage container 5 is provided with a molten alloy discharge nozzle 6 at its bottom, and the molten alloy 3 is further heated by a heating coil (not shown) and discharged from a slit 7 formed at the lower end of the molten alloy discharge nozzle 6 onto the surface (outer circumferential surface) of a chill roll 8. The molten alloy in contact with the surface of the chill roll 8 is rapidly cooled by supplying cooling water to the inside of the chill roll 8, forming a thin ribbon-like rapidly solidified alloy 9 of (Fe,Co)-B system. The material of the molten alloy discharge nozzle 6 can be appropriately selected from, for example, quartz (SiO2), boron nitride (BN), silicon carbide (SiC), and alumina (Al2O3).

[0034] FIG. 2 is an enlarged view of the discharge nozzle 6 of the device shown in FIG. 1, where (a) is a cross-sectional view and (b) is a bottom view. The discharge nozzle 6 shown in FIG. 2(a) is a single-slit nozzle in which a single slit 7 is formed. The width W1 of the slit 7 serves to adjust the discharge rate of the molten alloy 3 supplied to the chill roll 8. If the slit width W1 is too small, slit processing is likely to become difficult, and the slit 7 is likely to be blocked by the molten alloy. On the other hand, if the slit width W1 is too large, the discharge rate becomes too high, and the heat removal at the chill roll 8 is not enough, and the rapidly solidified alloy sticks to the chill roll 8, making it difficult to continue stable molten rapid solidification. Therefore, the slit width W1 is 0.2 mm or more and 0.7 mm or less. The slit width W1 is preferably 0.3 mm or more and 0.6 mm or less, and more preferably 0.3 mm or more and 0.5 mm or less.

[0035] The molten metal supplied to the surface of the chill roll 8 becomes a thin ribbon-shaped rapidly solidified alloy 9 by the rotation of the chill roll 8, and is peeled off from the chill roll 8. If the surface speed of the chill roll 8 is too low, the (Fe,Co)-B-based rapidly solidified alloy becomes excessively thick, exceeding 50 μm, and a coarse α-Fe phase precipitates, which makes it easy for cracks to occur during punching press. On the other hand, if the surface speed of the chill roll 8 is too high, the (Fe,Co)-B-based crystalline alloy becomes too fine, and the abundance ratio of the α-Fe phase decreases, making it difficult to ensure Bs≧1.7T. For this reason, the surface speed of the chill roll 8 is 15 m / sec or more and 40 m / sec or less, preferably 15 m / sec or more and 35 m / sec or less, and more preferably 17 m / sec or more and 32 m / sec or less. The diameter of the chill roll 8 is, for example, 200 to 20,000 mm. The cooling roll 8 does not necessarily need to be water-cooled if the quenching and solidification time is short, 10 seconds or less, but if the quenching and solidification time is 10 seconds or more, it is preferable to suppress the temperature rise on the surface of the cooling roll 8 by running cooling water inside the cooling roll 8. It is preferable to appropriately adjust the water-cooling capacity of the cooling roll 8 according to the latent heat of solidification and the molten metal tapping rate per unit time.

[0036] In producing the ribbon-shaped rapidly solidified alloy 9, the adhesion of the molten alloy 3 to the outer surface of the chill roll 8 is important, but this adhesion of the molten alloy is largely dependent on the surface roughness of the chill roll 8. If the surface roughness of the chill roll 8 is too small, the molten alloy 3 will slip on the surface of the chill roll 8, making sufficient cooling difficult, whereas if the surface roughness of the chill roll 8 is too large, the quenched alloy may stick to the chill roll 8. For this reason, the arithmetic mean roughness (Ra) of the surface of the chill roll 8 is 0.01 μm or more and 0.6 μm or less, preferably 0.05 μm or more and 0.55 μm or less, and more preferably 0.1 μm or more and 0.5 μm or less.

[0037] 1, if the distance d from the tip of the molten metal discharge nozzle 6 to the surface of the chill roll 8 is too small, the quenched alloy may stick to the chill roll 8, making it difficult to continue stable rapid solidification of the molten alloy 3, whereas if the distance is too large, a puddle may not be formed on the surface of the chill roll 8, making it difficult to rapidly solidify the molten alloy 3. For this reason, the distance d is 0.2 mm or more and 5.0 mm or less, preferably 0.3 mm or more and 3.0 mm or less, and more preferably 0.3 mm or more and 2.0 mm or less.

[0038] The chill roll 8 is preferably made of a material whose main raw material is any one of pure copper, copper alloy, molybdenum (Mo) and tungsten (W), thereby providing excellent thermal conductivity and durability. The main raw material means that it accounts for 50% or more by weight. The surface of the chill roll 8 may be plated with chromium, nickel or an alloy of these, which increases the heat resistance and hardness of the surface of the chill roll 8 and suppresses melting and deterioration of the roll surface during rapid solidification.

[0039] [Heat treatment] In a preferred embodiment, the (Fe,Co)-B based rapidly solidified alloy is heat-treated at a constant temperature of 200°C to 700°C, which enables the removal of strain in the rapidly solidified alloy and further reduces iron loss. If the heat treatment temperature is less than 200°C, the effect of removing strain is small, and if it exceeds 700°C, the α-Fe phase becomes coarse, so that the brittleness of the rapidly solidified alloy increases and the rapidly solidified alloy is easily cracked during punching. The heat treatment temperature is preferably 300°C to 700°C, more preferably 400°C to 680°C. The heat treatment time of the heat treatment depends on the shape of the soaking zone of the heat treatment device, but an optimal heat treatment time is appropriately selected within a time range of 3 minutes to less than 2 hours. The heat treatment is preferably performed in a vacuum or inert gas atmosphere, but heat treatment in the air is also acceptable.

[0040] [Example] The present invention will be described in more detail below with reference to examples, although the present invention is not limited to the following examples.

[0041] 100 kg of raw materials containing B, C, Co, and Fe with a purity of 99.5% or more were placed in an alumina crucible (melting furnace) and melted by high-frequency induction heating to form a molten alloy, so as to obtain the alloy compositions shown in Examples 1-11 and Comparative Examples 12-17 in Table 1 below. 50 kg of this molten alloy was poured into an alumina storage vessel with an inner diameter of 200 mm and a height of 400 mm, which was equipped at the bottom with a BN discharge nozzle having a slit as shown in Table 1. The slit width and slit length of the discharge nozzle were as shown in Table 1.

[0042] After this, 50 kg of the molten alloy was further heated by passing electricity through the high-frequency heating coil installed around the molten alloy storage vessel. After the temperature of the molten alloy reached a temperature 100°C higher than the melting point of the alloy composition, the alumina molten alloy stopper placed on the top of the discharge nozzle was pulled out. This caused the molten alloy to be ejected from the discharge nozzle onto the surface of the chill roll directly below. The chill roll was made of chrome zirconium copper and had an outer diameter of 600 mm and a width of 200 mm. The gap between the discharge nozzle and the chill roll surface is as shown in Table 1. The ejection pressure of the molten alloy from the discharge nozzle, the roll surface speed of the chill roll, and the arithmetic mean roughness (Ra) of the roll surface of the chill roll are as shown in Table 2.

[0043] The molten alloy ejected onto the surface of the chill roll formed a puddle on the surface of the chill roll and was rapidly solidified at the interface between the puddle and the chill roll, obtaining a ribbon-shaped rapidly solidified alloy having the average thickness and average width shown in Table 3. For Example 3, the rapidly solidified alloy was subjected to a heat treatment at 650°C for 10 minutes in an Ar flow. A punching test was performed on the rapidly solidified alloy thus obtained, with the results shown in Table 3.

[0044] The rapidly solidified alloys obtained were subjected to a structural evaluation by powder X-ray diffraction (XRD), and all of the rapidly solidified alloys of Examples 1-11 were crystalline alloys composed of α-Fe and Fe-B type compounds. The volume percentage of α-Fe precipitated in the rapidly solidified alloys (the ratio of α-Fe present was determined by X-ray diffraction) is shown in Table 3. Quantitative analysis of the constituent phases by powder X-ray diffraction is a common evaluation method, and can be incorporated into the analysis software of an X-ray diffraction device to grasp the composition ratio of each phase. As representative examples of the powder X-ray diffraction profiles of the rapidly solidified alloys of the examples, Example 4 is shown in FIG. 3 and Example 9 is shown in FIG. 4, respectively. As shown in FIG. 3 and FIG. 4, the structures of the rapidly solidified alloys of Examples 4 and 9 were composite structures composed of α-Fe and Fe-B phases.

[0045] Table 4 shows the Bs, core loss and magnetic permeability of the as-spun (immediately after rapid solidification) or heat-treated rapidly solidified alloys of Examples 1-11 and Comparative Examples 12-17. Bs was measured using a vibration type sample magnetometer manufactured by Toei Kogyo Co., Ltd., and core loss and magnetic permeability were measured using a BH analyzer manufactured by Iwasaki Electric Co., Ltd. As described above, only the rapidly solidified alloy of Example 3 was subjected to heat treatment, and as shown in FIG. 5, the powder X-ray diffraction profile of the rapidly solidified alloy of Example 3 also showed a composite structure consisting of α-Fe phase and Fe-B phase.

[0046] The rapidly solidified alloys of Comparative Examples 12-17 were found to have an amorphous single-phase metal structure by powder X-ray diffraction (XRD). Table 3 shows the volume percentage of α-Fe (the α-Fe abundance ratio was determined by X-ray diffraction). Figure 6 shows Comparative Example 12 as a representative example of the powder X-ray diffraction profile of the rapidly solidified alloy of the comparative example. As shown in Figure 6, the structure of the rapidly solidified alloy of Comparative Example 12 was an amorphous single-phase structure.

[0047] [Table 1]

[0048] [Table 2]

[0049] [Table 3]

[0050] [Table 4] [Explanation of symbols]

[0051] l Single roll molten metal quenching device 2 Melting furnace 3 Molten alloy 4 Tilt axis 5. Hot water container 6. Water outlet nozzle 7 Slit 8. Cooling roll 9 Rapidly solidified alloys

Claims

1. Composition formula (Fe 1-y Co y ) 100-x (B 1-z C z ) x where x, y, and z are respectively expressed as 10.0≦x≦18.0 atomic%, 0.05≦y≦0.5, 0.0≦z≦0.3 Satisfied, An iron-based crystalline alloy in which the abundance ratio of the α-Fe phase is 50 volume % or more and less than 95 volume %, and the remainder is Fe-B phase.

2. 2. The iron-based crystalline alloy according to claim 1, having a saturation magnetic flux density of 1.7 T or more, an iron loss (W10 / 1k) of 20 W / kg or less at a magnetic flux of 1.0 T and a frequency of 1 kHz, and a magnetic permeability of 1500 or more at 1 kHz.

3. Composition formula (Fe 1-y Co y ) 100-x (B 1-z C z ) x preparing a molten alloy of (Fe, Co)-B system having a composition where x, y, and z satisfy 10.0≦x≦18.0 atomic %, 0.05≦y≦0.5, and 0.0≦z≦0.3, respectively; a rapid solidification step of rapidly solidifying the molten alloy on a cooling roll, The rapid solidification step includes a step of spraying the molten alloy from a tapping nozzle onto the surface of the chill roll while rotating the chill roll at a roll surface speed of 15 m / sec to 40 m / sec, thereby producing an iron-based crystalline alloy in which the abundance ratio of α-Fe phase is 50 volume % or more and less than 95 volume %, and the remainder is Fe-B phase.

Citation Information

Patent Citations

  • Iron - cobalt - based toughness nanocrystalline soft magnetic alloy and preparation method thereof

    CN107103976A

  • Method for manufacturing fe-base soft magnetic alloy magnetic core

    JP2002053939A

  • iron-based alloys

    JP2022523627A

  • Method for producing fe-si-b-based thick rapidly solidified alloy thin strip

    WO2022196672A1

  • Production of metal strip and nozzle for production

    JP1988220950A